Evaluation of Ceruloplasmin Oxidase Activity in Sera of Breast Cancer Individuals in Kurdistan Region/ Iraq - Rozoqi, Shahlaa Shafiq (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2021)
Ceruloplasmin is considered the main copper transport protein which is proposed to have a role in cancer. Ceruloplasmin is an acute phase reactant and antioxidant enzyme, has been found to be increased in sera of patients with several types of cancers including breast cancer.The aim of present study was to determine of ceruloplasmin oxidase activity, specific activity, iron concentration in sera of patients with breast cancer and comparing with healthy group, and the ability of using enzyme as a tumor marker for breast cancer.This study was performed from November 2018 to January 2019, blood samples were collected from breast cancer patients in Nanakeli Hospital in Erbil city. Study was included (65) female patients with breast cancer and (20) healthy donors as control group. Ceruloplasmin activity, specific activity, serum total protein concentration, serum total iron concentration levels were estimated for all samples by colorimetric methods. The results shown that there was a significant increase in ceruloplasmin activity level for patients with breast cancer ( 227.8 U/L) compared with control group (101.1 U/L) while total protein level for breast cancer  patients (6.592 g/dl) showed no significant change compared to control group(7.127 g/dL) likewise the result shown that there was a significant increase in specific activity of ceruloplasmin and total iron concentration level for patients with breast cancer (34.74 U/mg) (334.2 mg/dl) compared to control group (14.14 U/mg) (128.6 mg/dl) The conclusion of this study was the concentration of ceruloplasmin activity, serum total iron concentration and specific activity of ceruloplasmin significantly increase in breast cancer patients while total protein level revealed no significant change.Serum ceruloplasmin oxidase activity and specific activity were highly significant elevated in patient group when compared with control group. Also the total iron concentration results showed significant increasing (PË‚0.0001) between of patient with breast cancer and control group.